Processing and Nutritional Value of Corn By-Product as Ruminant Feed - Uum Umiyasih; Elizabeth Wina (Indonesian Center for Animal Research and Development, 2008)
Corn is a commodity that can be used as food or feed since in some areas, it sometimes replaces rice as the staple food and is also required as feed ingredient especially for poultry. There are several kinds of by-products produced after corn harvest and from corn based industry. These by-products are very potential to be used as ruminant feed. Nutritional quality of corn by-products varies but is not high enough to be used as a sole diet. To optimize its utilization, by-products quality should be improved and should be supplemented by other feed ingredients. Simple preservation technology of corn by-products should be continously disseminated and done by farmers to provide sustainable feed for their livestock during dry season. Key words: Corn by-products, feed, ruminant